Preparation method and application of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheet composites
By embedding amorphous CoS nanodots in the two-dimensional nitrogen-sulphur double-doped carbon nanosheets, the CoS NDs/NSCN composite material is formed, and the problems of CoS materials in the negative electrode field of lithium-ion batteries are solved, and high specific capacity and excellent cycling and rate performance are achieved.
Patent Information
- Application Number
- CN202210890191.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-07-27
AI Technical Summary
The existing CoS materials have problems such as poor conductivity, obvious volume effects, and insufficient exposure of lithium storage sites in the negative electrode of lithium-ion batteries, resulting in poor performance in cycling and rate performance.
By embedding amorphous CoS nanodots in the two-dimensional nitrogen-sulphur double-doped carbon nanosheets, the CoS nanodots and two-dimensional carbon nanosheets are pyrolyzed at high temperatures using a salt template to form the CoS nanodots and two-dimensional carbon nanosheets to form the CoS NDs/NSCN composite material.
This method simplifies the process flow, reduces costs, improves the specific capacity and rate performance of the material, and the chemical bond between the carbon matrix and CoS inhibits the agglomeration of CoS, improving the cyclic stability of the material.
Smart Images

Figure CN115133000B_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of metal sulfide-based composite materials, and in particular to a preparation method and application of a composite material of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets. [Background technology]
[0002] Energy is the basic driving force of social development. How to develop and utilize renewable clean energy to alleviate the shortage of traditional fossil energy has gradually become the focus of human society. Batteries, as a device that can convert chemical energy into electrical energy, have the advantages of high energy conversion efficiency and environmental friendliness, and have attracted much attention in the fields of military aviation and civilian life.
[0003] Compared with traditional battery systems (such as lead-acid batteries and nickel-cadmium batteries), lithium-ion batteries (LIB) have advantages such as higher theoretical energy density, longer cycle life and no memory effect, making them the most successful battery system for commercial use. Graphite, as a negative electrode for commercial LIB, has a low theoretical specific capacity (372mAh g -1 ) have greatly hindered their application in the field of large-scale energy storage.
[0004] Metal sulfides, as a type of LIB negative electrode material that stores energy based on a phase transformation reaction mechanism, have a high theoretical discharge capacity and are considered a potential substitute for graphite negative electrodes. As a typical representative of metal sulfides, CoS has attracted much attention in the field of LIB negative electrodes. However, pure CoS is a semiconductor with poor conductivity, obvious volume effect during charge and discharge, and is easy to agglomerate during the preparation process, making it difficult to effectively expose lithium storage sites. Therefore, it often exhibits low discharge capacity and poor cycle and rate performance.
[0005] In order to improve the lithium storage performance of CoS, the commonly used modification strategies can be divided into three categories: (1) introducing a conductive carbon matrix. The composite of CoS and conductive carbon to obtain a CoS / C composite material can effectively improve the conductivity of CoS and alleviate its volume effect during the charge and discharge process to a certain extent; (2) regulating the microstructure. For example, designing a special amorphous structure, nanodot structure, etc. can shorten the ion diffusion path, expose the lithium storage sites of the material, and thus improve its lithium storage capacity and rate performance; (3) optimizing the chemical composition. For example, non-metallic doping is implemented in the CoS / C composite material. The heteroatoms (such as N, S, P, etc.) added to the carbon matrix can form chemical bonds with CoS, which is convenient for anchoring CoS particles and thus enhancing its cycle stability. At present, most studies are limited to one or two modification strategies, and the modification methods involved are complex and have poor controllability. In addition, the raw material utilization rate is not high, making it difficult to achieve large-scale commercial use.
[0006] Patent CN201610931981.0 discloses a preparation method and application of CoS@carbon nano cage composite material, comprising the following steps: (1) Co(NO 3 ) 2 6H 2 O and 2-methylimidazole were dissolved in deionized water, and Co(NO 3 ) 2 6H 2 O solution was added dropwise to the 2-methylimidazole solution, and then polyvinyl pyrrolidone was added and stirred at 25°C for 6-12 hours. The reaction product was washed with deionized water and ethanol for 3 times and then dried. It was calcined in a tube furnace at 550-650°C for 4-6 hours to obtain Co@carbon nanocages. (2) A certain amount of Co@carbon nanocages was weighed and mixed with sulfur powder and ground for 30-40 minutes. The ground sample was calcined in a tube furnace at 360-450°C for 2-5 hours to obtain a CoS@carbon nanocage composite material that can be used as a negative electrode for lithium-ion batteries.
[0007] However, it has the following disadvantages: the entire preparation process is relatively complicated, the cost is high, the operability is not strong, the sulfur source in the sulfurization process is single (only sulfur powder), and the CoS particles in the final product are relatively large, and the carbon matrix is not non-metallic doped, so the lithium storage performance of the material is limited.
[0008] Patent CN201811321281.5 discloses a method for preparing a bifunctional cobalt sulfide and sulfur- and nitrogen-doped carbon in-situ composite electrode. The specific synthesis steps are: (1) dissolving cobalt nitrate in deionized water, and using electrodeposition to grow a flaky cobalt hydroxide array on a conductive substrate, and then annealing the cobalt hydroxide array in air to form a porous, flaky cobalt oxide array. The electrodeposition time is 90 to 360 seconds, and the potential range of the working electrode relative to the saturated calomel electrode is -0.9 to -1.2 V. The air annealing temperature is 300 to 500°C, and the reaction time is 0.5 to 2 hours; (2) depositing polyaniline on the substrate on which the cobalt oxide array is grown, and then annealing in a sulfur atmosphere in an inert atmosphere to obtain a cobalt sulfide and sulfur- and nitrogen-doped carbon in-situ composite electrode with oxygen catalysis bifunctionality.
[0009] However, it has the following disadvantages: the entire material preparation process is relatively complicated, the operating conditions are relatively harsh, it involves an electrodeposition process, the controllability is not strong, the yield of the target product is low, and it is difficult to promote on a large scale; and the obtained composite electrode is used in the field of electrocatalysis, and there is no corresponding application research in the field of lithium-ion battery negative electrodes. [Summary of the invention]
[0010] The main purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a composite material of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets (CoS NDs / NSCN) with excellent lithium storage performance. The present invention has simple process, low cost, strong operability, high raw material utilization rate, and the salt template used can be recycled and reused. The obtained CoS NDs / NSCN composite material has broad application prospects in the field of lithium-ion batteries.
[0011] In order to achieve the purpose of the present invention, the following technical solutions are provided:
[0012] A preparation method and application of a composite material of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets, comprising the following steps:
[0013] (1) Weighing 0.1-0.6 g of a cobalt source, 0.2-0.4 g of a sulfur source, 0.1-0.3 g of a carbon source, and 1.0-4.0 g of a salt template respectively, and mechanically grinding them in a mortar for 10-15 minutes to obtain a uniformly mixed precursor powder;
[0014] (2) Pyrolyzing the precursor powder obtained in step (2) at 700-1000° C. in an inert atmosphere for 1-3 h to obtain a black pyrolysis product. During the high-temperature pyrolysis process, the cobalt source and the sulfur source can combine to form CoS; and the salt template is heated to a molten state, which can not only disperse the cobalt source and the sulfur source to promote the formation of CoS nanodots, but also serve as a growth director for carbon materials to form two-dimensional carbon nanosheets;
[0015] (3) The pyrolysis product obtained in step (2) is washed with deionized water for 3 to 4 times to remove the salt template, and then subjected to vacuum drying to finally obtain an amorphous CoS nanodot-embedded two-dimensional nitrogen-sulfur dual-doped carbon nanosheet composite material.
[0016] Preferably, the carbon source is a mixture of one or more of glucose, fructose, sucrose, chitosan, yeast, cellulose, starch and citric acid.
[0017] Preferably, the salt template includes a lithium salt template, a sodium salt template and a potassium salt template. The lithium salt template is a mixture of one or more of lithium chloride, lithium nitrate and lithium sulfate; the sodium salt template is a mixture of one or more of sodium chloride, sodium nitrate and sodium sulfate; the potassium salt template is a mixture of one or more of potassium chloride, potassium nitrate and potassium sulfate.
[0018] Preferably, the sulfur source is a mixture of one or more of thiourea, sulfur powder, thioacetamide, sodium sulfide and hydrogen sulfide.
[0019] Preferably, the cobalt source is a mixture of one or more of cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, cobalt chloride hexahydrate, cobalt oxalate dihydrate, and cobalt sulfate heptahydrate.
[0020] Preferably, the inert atmosphere is a mixture of one or more of nitrogen, argon and helium.
[0021] The amorphous CoS nanodots embedded in the two-dimensional nitrogen-sulfur dual-doped carbon nanosheet composite material prepared by the method of the present invention are beneficial to fully expose the lithium storage sites, shorten the ion transmission path, and improve the specific capacity and rate performance of the material, and can be applied to lithium ion negative electrode materials.
[0022] The present invention has the following beneficial effects:
[0023] (1) The target product has a simple synthesis process, low preparation cost, strong operability, high raw material utilization rate, and is convenient for large-scale macro-preparation. The salt template used can be recycled.
[0024] (2) The CoS in the target product has an amorphous nanodot structure, which is conducive to fully exposing the lithium storage sites, shortening the ion transmission path, and improving the specific capacity and rate performance of the material; at the same time, the carbon matrix in the composite material is a two-dimensional nitrogen-sulfur co-doped carbon nanosheet, which can form a chemical bond with CoS, facilitating the anchoring of CoS nanodots and inhibiting their agglomeration, thereby hopefully obtaining a CoS NDs / NSCN composite LIB negative electrode with high specific capacity and excellent cycle and rate performance, which has a good application prospect in lithium-ion battery negative electrode materials.
[0025] The features and advantages of the present invention will be described in detail through embodiments in conjunction with the accompanying drawings.
Brief Description of the Drawings
[0026] Figure 1 SEM images of Co nanoparticles / nitrogen-sulfur dual-doped carbon (Co / NSC) (a) prepared without salt template in Example 1 and amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets (CoS NDs / NSCN–1mmol, 1mmol refers to the amount of Co source added) (b) prepared using NaCl salt template.
[0027] Figure 2 TEM (a), HRTEM (b), SAED (c) and elemental distribution spectrum (d) of CoS NDs / NSCN-1mmol prepared in Example 1.
[0028] Figure 3 XRD spectra of CoS NDs / NSCN–1mmol (a) and Co / NSC (b) prepared in Example 1.
[0029] Figure 4 Raman spectra of CoS NDs / NSCN-1mmol and Co / NSC prepared in Example 1.
[0030] Figure 5 (a) and (b) the XPS full spectrum and S 2p high-resolution spectrum of CoS NDs / NSCN-1mmol prepared in Example 1.
[0031] Figure 6 The cycling performance (a) and rate performance diagram (b) of the CoS NDs / NSCN-1mmol and Co / NSC electrodes prepared in Example 1.
[0032] Figure 7 SEM (a) and TEM (b) images of the amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheet composite material (CoS NDs / NSCN-0.5mmol, 0.5mmol refers to the amount of Co source added) prepared using the NaCl template in Example 2.
[0033] Figure 8 XRD (a) and Raman (b) spectra of CoS NDs / NSCN-0.5mmol prepared in Example 2.
[0034] Fig. 9 The cycling performance (a) and rate performance (b) of the CoS NDs / NSCN-0.5mmol electrode prepared in Example 2.
[0035] Fig.10 XRD (a) and Raman (b) spectra of the amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheet composite material (CoS NDs / NSCN-2mmol, 2mmol refers to the Co source addition amount) prepared using KCl template in Example 3.
[0036] Fig.11 The cycling performance (a) and rate performance diagram (b) of the CoS NDs / NSCN-2mmol electrode prepared in Example 3. [Specific implementation method]
[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0038] In the description of the present invention, it should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it may be directly connected to the other element or indirectly connected to the other element.
[0039] In the description of the present invention, it should be noted that the terms "center", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, or the positions or positional relationships in which the invention product is usually placed when in use, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third" and the like are only used to distinguish descriptions, and cannot be understood as indicating or implying relative importance. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, "multiple" means two or more, unless otherwise clearly and specifically defined. "Several" means one or more, unless otherwise clearly and specifically defined.
[0040] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0041] Embodiment 1:
[0042] 0.29g of cobalt nitrate hexahydrate (1mmol), 0.30g of thiourea, 0.15g of sucrose and 3.0g of sodium chloride were weighed and ground in a mortar for 15 minutes to obtain a precursor powder; the precursor powder was transferred to a tube furnace and calcined at 900℃ for 2h under an argon atmosphere to obtain a black pyrolysis product; the obtained black pyrolysis product was repeatedly washed with deionized water for 3 to 4 times to remove the salt template, and then vacuum dried to obtain the product CoS NDs / NSCN-1mmol. For comparison, the product Co / NSC was synthesized using a similar process without the addition of sodium chloride template.
[0043] See also Figure 1, as shown in the figure are the SEM (scanning electron microscope) images of Co / NSC (a) and CoS NDs / NSCN–1mmol (b) composite materials. Figure 1 a It can be seen that the microstructure of Co / NSC is a stacked carbon block, while the microstructure of CoS NDs / NSCN–1mmol is a typical two-dimensional carbon sheet.
[0044] See also Figure 2 , as shown in the figure are TEM (a) (transmission electron microscopy), HRTEM (b) (high-resolution transmission electron microscopy), SAED (c) (selected area electron diffraction) and element distribution spectrum (d) of CoS NDs / NSCN–1mmol. Figure 2 a shows that the sample is a thin two-dimensional carbon sheet structure; Figure 2 b It can be seen that amorphous CoS NDs with a diameter of about 4nm are dispersed on the surface of the carbon sheet. This special amorphous structure can also be confirmed by the SAED pattern. From the element distribution diagram, it can be seen that C, Co, N, O and S elements exist in the sample, indicating that carbon sheets and CoS may exist in the sample.
[0045] See also Figure 3 , Figure 3 a is the XRD diagram of CoS NDs / NSCN–1mmol. As can be seen from the figure, the sample shows typical CoS characteristic diffraction peaks at 2θ=31°, 35°, 47° and 54°, indicating the successful synthesis of CoS. At the same time, it was found that the characteristic diffraction peak of CoS was weak, indicating its special amorphous nature. Figure 3b is the XRD diagram of Co / NSC. As can be seen from the figure, the product synthesized without introducing a salt template is Co / NSC.
[0046] See also Figure 4 , as shown in the figure are the Raman images of CoS NDs / NSCN–1mmol and Co / NSC composite materials. It can be seen from the figure that the CoS NDs / NSCN–1mmol sample has a Raman peak at 680 cm -1 A characteristic peak of CoS appears at 1350cm and 1590cm in the Raman graph of Co / NSC. -1 Typical carbon material D band and G band appear at the bottom. Usually, the peak intensity ratio of the D band and the G band (I D / I G ) can reflect the degree of defects in the material. Compared with Co / NSC (ID / IG=0.92), the ID / IG value of CoS NDs / NSCN–1mmol increased to 1.03, indicating that it has a higher degree of defects.
[0047] See also Figure 5, as shown in the figure are the full XPS spectrum (a) and S 2p high-resolution spectrum (b) of CoS NDs / NSCN–1mmol. Figure 5 From a, we can see that there are C, N, O, S and Co elements in this material. Figure 5 b It can be seen that the S element in this material has three different configurations: S 2– , C–S and S–Co / C–S–Co. The existence of the C–S configuration indicates that the S element is successfully doped into the carbon material structure, while the existence of the C–S–Co configuration indicates that a chemical bond is formed between the carbon material and CoS, which can be used to strengthen the anchoring of CoSNDs and inhibit their aggregation.
[0048] See also Figure 6 , as shown in the figure are the cycling performance (a) and rate performance (b) of CoS NDs / NSCN–1mmol and Co / NSC electrodes. Figure 6 It can be seen that the initial discharge capacity of the Co / NSC electrode is 862.4 mAh g –1 After 400 cycles, its discharge capacity is only 312.6 mAh g –1 In contrast, the initial discharge capacity of the CoS NDs / NSCN–1mmol electrode is 1165.3mAh g –1 After 400 cycles, it still remains at 674.8 mAh g –1 , indicating its excellent cycle stability. Figure 6 b It can be seen that compared with the Co / NSC electrode, the CoS NDs / NSCN–1mmol electrode exhibits higher discharge specific capacity at different current densities, indicating its better rate performance.
[0049] Embodiment 2:
[0050] 0.15 g of cobalt nitrate hexahydrate (0.5 mmol), 0.30 g of thiourea, 0.15 g of sucrose and 3.0 g of sodium chloride were weighed respectively, and ground evenly in a mortar (at least for 10 minutes) to obtain a precursor powder; the precursor powder was placed in a tube furnace and calcined at 900 °C for 3 h under a nitrogen atmosphere; the obtained pyrolysis product was repeatedly washed 3 times with deionized water to remove the salt template, and then vacuum dried to obtain the product CoS NDs / NSCN –0.5 mmol.
[0051] See also Figure 7 , as shown in the figure are the SEM image (a) and HRTEM image (b) of the CoS NDs / NSCN–0.5mmol composite material. Figure 7 a It can be seen that the microstructure of CoS NDs / NSCN–0.5mmol is a typical two-dimensional carbon sheet structure; Figure 7b It can be seen that amorphous CoS NDs with a diameter of about 6 nm are dispersed on the surface of the two-dimensional carbon sheet.
[0052] See also Figure 8 , as shown in the figure are the XRD (a) and Raman (b) spectra of CoS NDs / NSCN–0.5mmol composite material. Figure 8 a It can be seen that the sample only has a typical carbon diffraction peak at 2θ = 26°, and no obvious CoS characteristic peak appears; Figure 8 b shows that the sample is at ~680cm -1 A typical CoS Raman characteristic peak appears at the surface, and the above results confirm the formation of amorphous CoS in the sample.
[0053] See also Fig. 9 , as shown in the figure are the cycling performance (a) and rate performance (b) of the CoS NDs / NSCN–0.5mmol electrode. Fig. 9 It can be seen that the initial discharge capacity of the CoS NDs / NSCN–0.5mmol electrode is 816.4mAh g–1, and after 135 cycles, its discharge capacity remains at 434.8mAh g –1 ; and the Coulomb efficiency increased by nearly 100%, indicating the excellent cycle stability and reversibility of the sample. Fig. 9 b It can be seen that the discharge capacity of CoS NDs / NSCN–0.5mmol electrode is 355.3mAh g at a current density of 0.1A / g –1 When the current density increases to 1.6A / g, its discharge capacity still reaches 229.2mAh g –1 When the current density returns to 0.1A / g, the discharge capacity can be restored to 348.5mAh g –1 , indicating its excellent rate performance.
[0054] Embodiment 3:
[0055] 0.58 g of cobalt nitrate hexahydrate (2 mmol), 0.30 g of thiourea, 0.15 g of sucrose and 2.0 g of potassium chloride were weighed respectively and ground evenly in a mortar (about 15 minutes) to obtain a precursor powder; the precursor powder was placed in a tube furnace and calcined at 800 ° C for 2 h under a nitrogen atmosphere; the obtained pyrolysis product was repeatedly washed with deionized water for 3 times to remove the salt template, and then vacuum dried to obtain the product CoS NDs / NSCN –2mmol (KCl).
[0056] See also Fig.10 , as shown in the figure are the XRD (a) and Raman (b) spectra of CoS NDs / NSCN–2mmol(KCl) composite materials. Fig.10a It can be seen that the sample exhibits the typical characteristic peaks of CoS, but the diffraction peak intensity is very weak, indicating its amorphous characteristics; at the same time, Fig.10 b medium~680cm -1 The Raman characteristic peak of CoS appears at , which also proves the successful preparation of CoS.
[0057] See also Fig.11 , as shown in the figure are the cycling performance (a) and rate performance (b) of the CoS NDs / NSCN–2mmol(KCl) electrode. Fig.11 a It can be seen that the initial discharge capacity of CoS NDs / NSCN–2mmol(KCl) electrode is 536.4mAh g –1 After 220 cycles, the discharge capacity reached 289.3 mAh g –1 .Depend on Fig.11 b It can be seen that after the charge and discharge test at different current densities, the electrode still has a good discharge specific capacity, indicating its good rate performance.
[0058] The cobalt nitrate hexahydrate in the above embodiment may also be replaced by other cobalt sources, and the cobalt source may be a mixture of one or more of cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, cobalt chloride hexahydrate, cobalt oxalate dihydrate, and cobalt sulfate heptahydrate.
[0059] The thiourea in the above embodiment may also be replaced by other sulfur sources, such as thiourea, sulfur powder, thioacetamide, sodium sulfide, or a mixture of one or more of hydrogen sulfide.
[0060] The sucrose in the above embodiment may also be replaced by other carbon sources, and the carbon source may be a mixture of one or more of glucose, fructose, sucrose, chitosan, yeast, cellulose, starch, and citric acid.
[0061] The potassium chloride in the above embodiment can also be replaced with other salt templates, including lithium salt templates, sodium salt templates and potassium salt templates. The lithium salt template is a mixture of one or more of lithium chloride, lithium nitrate and lithium sulfate. The sodium salt template is a mixture of one or more of sodium chloride, sodium nitrate and sodium sulfate. The potassium salt template is a mixture of one or more of potassium chloride, potassium nitrate and potassium sulfate.
[0062] The inert atmosphere in the above embodiment may be a mixture of one or more of nitrogen, argon and helium.
[0063] Through the above three embodiments, it can be concluded that the CoS in the target product has an amorphous nanodot structure, which is conducive to fully exposing the lithium storage sites, shortening the ion transmission path, and improving the specific capacity and rate performance of the material; at the same time, the carbon matrix in the composite material is a two-dimensional nitrogen-sulfur dual-doped carbon nanosheet, which can form a chemical bond with CoS, which is convenient for anchoring CoS nanodots and inhibiting their agglomeration, and thus it is expected to obtain a CoS NDs / NSCN composite LIB negative electrode with high specific capacity and excellent cycle and rate performance, which has a good application prospect in lithium-ion battery negative electrode materials.
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite material of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets, characterized in that: The steps include: (1) Weigh 0.1-0.6 g of cobalt source, 0.2-0.4 g of sulfur source, 0.1-0.3 g of carbon source, and 1.0-4.0 g of salt template respectively, and grind them mechanically in a mortar for 10-15 min to obtain a uniformly mixed precursor powder; (2) pyrolyzing the precursor powder obtained in step (1) at 700-1000° C. in an inert atmosphere for 1-3 h to obtain a black pyrolysis product; (3) washing the pyrolysis product obtained in step (2) with deionized water for multiple times to remove the salt template, and then vacuum drying to finally obtain a composite material of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets; The sulfur source is a mixture of one or more of thiourea and thioacetamide; the salt template includes a lithium salt template, a sodium salt template, or a potassium salt template.
2. The method for preparing a composite material of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets according to claim 1, characterized in that: The cobalt source is a mixture of one or more of cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, cobalt chloride hexahydrate, cobalt oxalate dihydrate and cobalt sulfate heptahydrate.
3. The method for preparing a composite material of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets according to claim 1, characterized in that: The carbon source is a mixture of one or more of glucose, fructose, sucrose, chitosan, yeast, cellulose, starch and citric acid.
4. The method for preparing a composite material of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets according to claim 1, characterized in that: The lithium salt template is a mixture of one or more of lithium chloride, lithium nitrate and lithium sulfate; The sodium salt template is a mixture of one or more of sodium chloride, sodium nitrate and sodium sulfate; The potassium salt template is a mixture of one or more of potassium chloride, potassium nitrate and potassium sulfate.
5. The method for preparing a composite material of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets according to claim 1, characterized in that: The inert atmosphere is a mixture of one or more of nitrogen, argon and helium.
6. Use of the composite material of amorphous CoS nanodots embedded in two-dimensional nitrogen-sulfur dual-doped carbon nanosheets according to any one of claims 1 to 5 in negative electrode materials for lithium-ion batteries.
Citation Information
Patent Citations
Cos@carbon nano-cage as well as preparation method and application thereof
CN106450200A
Preparation method of bifunctional cobalt sulfide, sulfur and nitrogen doped carbon in-situ composite electrode
CN109585856A
High-performance cobalt particle modified nitrogen doped carbon nanosheet lithium oxygen battery cathode catalyst material and preparation method thereof
CN108400343A
Preparation method and application of sulfur-nitrogen co-doped three-dimensional porous carbon nanosheet
CN111825074A